2012
DOI: 10.3928/01913913-20110614-01
|View full text |Cite
|
Sign up to set email alerts
|

Lenticular Abnormalities in Children

Abstract: Developmental and posttraumatic cataracts were the most common abnormalities. Delayed presentation is of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…One study in India was a retrospective review of patients seeking treatment at the hospital regardless of whether they had undergone cataract surgery. 43 Comparing data by region shows that the proportion of children undergoing surgery who were girls in the following regions were comparable to the proportion in high-income, gender-neutral countries: the Middle East, North Africa, and Central Asia region (48.6%) and in the Latin America and Caribbean region (43.7%), but were significantly lower in all other regions: sub-Saharan Africa (41.1%), East Asia and the Pacific (all from China; 36.0%), and South Asia (29.1%; Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…One study in India was a retrospective review of patients seeking treatment at the hospital regardless of whether they had undergone cataract surgery. 43 Comparing data by region shows that the proportion of children undergoing surgery who were girls in the following regions were comparable to the proportion in high-income, gender-neutral countries: the Middle East, North Africa, and Central Asia region (48.6%) and in the Latin America and Caribbean region (43.7%), but were significantly lower in all other regions: sub-Saharan Africa (41.1%), East Asia and the Pacific (all from China; 36.0%), and South Asia (29.1%; Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a disadvantage of this technique is that it currently cannot detect large amblyogenic refractive errors caused by lenticular abnormalities [42] (e.g., cataract, posterior lenticonus, and Marfan syndrome). Although these situations are rare, it is essential to consider this disadvantage if this technique is to be used in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study completed at our center on the lenticular abnormalities in children resulted in males constituting 66% of the patients. 9 A study performed in the United Kingdom by Rahi and Dezateux 3 resulted in a median age of detection at 8 weeks. The delay in detection and subsequent presentation in our study can be attributed to the lack of awareness and poor literacy levels, as shown in a study by Mwende et al 2 In a retrospective analysis of 59 patients with congenital cataract conducted by Fakhoury et al, 10 it was observed that leukocoria and strabismus led to a diagnosis in 24% and 19% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%